DUKUNGAN PERILAKU POSITIF OLEH GURU UNTUK MENGURANGI PERILAKU MENGABAIKAN TUGAS PADA SISWA SMA NEGERI 3 BANJARMASIN - Agustina, Hellya (Faculty of Ushuluddin and Humanities, 2013)
This research aimed to examine positive behavioral support by teacher had been trained to reduce off-task behavior students. The participants of students was second grade of senior high school at Banjarmasin. The reason for using this design was to identifiying behavior target repeatedly with a certain time period. The instruments was be used to take data from observation form positive behavioral support and off-task behavior. The result ofanalysis data was by using visual analysis and qualitative analysis. From two of analysis indicated that there was different between before and after positive behavioral support implemented by teacher and off-task behavior of two students were reduced into lower frequency.